WEB-BASED INFORMATION SYSTEM DESIGN OF 3 KG LPG GAS DISTRIBUTION AT THE ARMY COOPERATIVE CENTRE AGENT - Rian Saputra; Danyl Mallisza; Nuraeni Dahri (Journal of Social and Economics Research, 2025)
The design of this web-based 3kg LPG gas distribution system specifically aims to create an effective and efficient gas distribution process, producing accurate reports. In general, the development of this distribution system is an effort to improve services to the community and UMKM that become agents. Problems with the conventional distribution system at the Army Cooperative Centre agents often result in invalid data and inaccurate information. The data management and distribution process has not been computerised online. This slows down the gas distribution reporting process, and weak monitoring services to all agents. The system design uses an online website platform. The system design method uses the System Development Life Cycle (SDLC), the model approach used is Waterfall with 5 stages, namely, a) Planning b) Analysis c) Design d) Implementation e) Maintance. The programming language used is PHP, and the database application uses MySql data processor. The conceptual design of the system uses Unifed Modeling Language (UML) using 4 (four) diagrams according to design needs, namely Usecase Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. The result of the design is a Web-based LPG 3 kg Gas Distribution System that can simplify the distribution process and produce reports that are fast, precise and accurate.